2021
DOI: 10.3389/feduc.2021.642861
|View full text |Cite
|
Sign up to set email alerts
|

Confronting COVID: Crisis Leadership, Turbulence, and Self-Care

Abstract: School leadership during the pandemic serves as the contextual backdrop for this conceptual article. Specifically, we believe the preparation of today’s school leaders must be re-examined to consider the inclusion of frameworks that consider not only how principals might navigate extreme crises but also how they look after themselves and their wellbeing in ways that may curb the chronic stress that often leads to professional burnout. In this article, we tie together three bodies of literature – crisis managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
(85 reference statements)
1
31
0
Order By: Relevance
“…Research shows that principals with high resilience have a strong ability to recover from stress and crisis and are more effective leaders ( Fletcher and Nicholas, 2016 ; Geer and Coleman, 2014 ). The parallel processes here are important: School principals not only endeavor to stand firm in the face of crisis themselves but also invest in building the collective-organizational resilience of their school and its stakeholders, namely students, staff, parents, and community ( Urick et al, 2021 ).…”
Section: Eight Guidelines For Leading a Pandemic Crisismentioning
confidence: 99%
“…Research shows that principals with high resilience have a strong ability to recover from stress and crisis and are more effective leaders ( Fletcher and Nicholas, 2016 ; Geer and Coleman, 2014 ). The parallel processes here are important: School principals not only endeavor to stand firm in the face of crisis themselves but also invest in building the collective-organizational resilience of their school and its stakeholders, namely students, staff, parents, and community ( Urick et al, 2021 ).…”
Section: Eight Guidelines For Leading a Pandemic Crisismentioning
confidence: 99%
“…Anderson et al (2020) stress the importance of self-care for principals, but found that principals prioritized the care of their stakeholders over their self-care. Urick et al (2021) offer four recommendations for supporting principals through crisis leadership, which include (a) prioritize communication; (b) establish values; (c) integrate planning and (d) promote self-care. Although the researchers in these studies identified the stressors and reactions of principals during the early months of the COVID-19 pandemic, little is known on how principals engaged in self-care practices and focused on their well-being.…”
Section: Principal Leadership and Covid-19 Pandemicmentioning
confidence: 99%
“…(2020) stress the importance of self-care for principals, but found that principals prioritized the care of their stakeholders over their self-care. Urick et al. (2021) offer four recommendations for supporting principals through crisis leadership, which include (a) prioritize communication; (b) establish values; (c) integrate planning and (d) promote self-care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, as schools closed during COVID-19, unanticipated crisis (e.g., school shootings, hurricanes, and wildfires), racial and social injustices became part of the national and international news [e.g., George Floyd, the border wall, criminal policies of (in)equity, (in)equality, and (in)justice], in addition to on-going technology issues in schools, all added emotional weight and turmoil to the public psyche, regardless of which side of the issues people espoused (Watson et al, 2019;Algar and Feis, 2020;Goldstein, 2020;Heitner, 2020;Hodges et al, 2020;Wilkerson, 2020;Reyes-Guerra et al, 2021;Virella and Cobb, 2021). Thus, conflicts will not cease to exist, however there are skills that can and should be taught via professional development that can provide opportunities to manage conflict, resulting in productive and constructive solutions (Coldwell et al, 2012;Jacques, 2012;Cohen et al, 2017;Watson et al, 2017;Hemmer and Elliff, 2019;Scott et al, 2021;Urick et al, 2021). As schools begin to shutter and close in March 2020, school leaders were tasked with transitioning quickly to online platforms.…”
Section: Conflict Managementmentioning
confidence: 99%
“…As schools begin to shutter and close in March 2020, school leaders were tasked with transitioning quickly to online platforms. This new normal also increased conflict and stress for an already burdened educational system and for a network of educators (Jacques, 2012;Cohen et al, 2017;Urick et al, 2021).…”
Section: Conflict Managementmentioning
confidence: 99%